Study of Morphology of Large Intestine in 50 Donated Embalmed Cadavers - Sawant , SharadKumar Pralhad; Rizvi , Shaheen (Current Progress in Medicine and Medical Research Vol. 9, 2023)
Aim: To study the morphology of large intestine to document the presence of any growth or bulge. Material and Methods: A study was conducted in the Department of Anatomy of K. J. Somaiya Medical College in which 50 large intestines from donated embalmed cadavers were examined for the presence of any growth or bulge. Results: In 5 cadavers a hard bulge was observed in the distal part of descending colon. On incising, a mass was observed in its posterior wall. It measured 5cm x 5cm encircling nearly half the lumen but not showing any signs of obstruction. Histopathology confirmed the diagnosis of adenocarcinoma. Clinical Significance: Colon Carcinoma involves genetic factors, environmental exposures, dietary habits, and inflammatory conditions of the gastrointestinal tract. Death from colon cancer usually results from metastases in the liver. Conclusions: As colon cancer is the most common carcinoma with high mortality rates, the cure is greater when the disease is detected at early stage. Early detection and screening is of great importance. Colonoscopy detects some colon polyps and cancers early enough that they may be treated.